PENGARUH UKURAN PERUSAHAAN, UKURAN KAP DAN AUDITOR INTERNAL TERHADAP AUDIT DELAY - Yennisa Yennisa (Jurnal Akuntansi, 2017)
The purpose of this research is to analyze the influence of firm size, size of Public Accountant firm, and internal auditors to audit delay. The sample of this research for used 29 manufacture companies sector of consumer goods that listed in Indonesia Stock Exchange (IDX) for the period 2012-2015. The hypothesis proposed were tested by multiple linier regressions models. The results of the research shows that firm size and internal auditors has influence to audit delay. While size of Public Accountant firms do not has influence to audit delay.